Coediting the Revista de Investigación Clínica with Ruben Lisker, 1974-1987 - Enrique Wolpert-Barraza (Permanyer, 2021)
Dear Editor, In 1970, I returned from Rochester, MN, US, after completion of two and a half years of medical residency in Gastroenterology at the Mayo Clinic.